Transition of a Primary Care Fellowship to A Virtual Format: Lessons Learned - Jeffrey Schlaudecker (Shiraz University of Medical Sciences, 2021)
The Community Primary Care Champions (CPCC) Fellowship program trains physicians and physician assistants to expand community underserved partnerships and healthcare transformation. The COVID-19 pandemic required a rapid transition to virtual platforms (e.g. Zoom) to facilitate the safe delivery of medical care and education. This report describes the resulting lessons learned in transitioning to a virtual fellowship. The fellowship involves self-directed learning, didactics, and smallgroup discussions. The first CPCC fellowship cohort included inperson instruction. A second cohort transitioned to a virtual-only format in March 2020 due to COVID-19. A third virtual-only cohort began in September 2020. Focus group data was analyzed for themes in the transition to a virtual format. Key lessons learned were derived during this transition including: 1) Realignment of focus of didactic and discussions for continued fellow engagement; 2) Leveraging virtual tools to optimize impact of activities; and 3) Geographic expansion of fellowship recruitment resulting in a more diverse cohort. A virtual fellowship has also allowed for refocused approaches to learning, building rapport, and an expanded reach in geography. This has enriched the experience of the fellowship by producing primary care champions in leadership and advocacy across practice environments. This supports retention of a virtual CPCC fellowship.